Republic of Serbia : Second Review Under the Stand-By Arrangement and Requests for Waiver of End-September Performance Criterion, Modification of End-December Performance Criteria, Rephasing of Purchases, and Financing Assurances Review. (IMF Staff Country Reports; Country Report ;, 2010)
Serbia's Second Review under the Stand-By Arrangement and requests for Waiver of Performance Criterion are examined. The contraction in GDP has been limited relative to regional comparators, but absorption and external trade have fallen faster than expected. Foreign parent banks have rolled over their external exposure vis-a-vis Serbia, as agreed under the Bank Coordination Initiative. Rapidly rising nonperforming loans and uncertainty over real sector prospects have crimped new credit, notwithstanding government efforts to support bank lending through interest subsidies and loan guarantees.